Isolation of a Suppressor Host Bacterium in Staphylococcus aureus - Kretschmer, P J. (1973)
A bacterial mutant of Staphylococcus aureus NCTC 8325 has been isolated which has the properties of a suppressor host mutant. The mutant was isolated as a one-step phenotypic revertant to wild type of a strain containing mutations in two unlinked markers concerned with metabolism of lactose via the phosphoenol pyruvate-dependent phosphotransferase system. The revertant (called sup1(+)) has been used to isolate seventy conditional lethal mutants of the phage O11. The phage mutants, which plate on sup1(+) but not on the original 8325 strain, have been assigned by complementation studies into 10 groups. It is probable that this technique for the isolation of suppressor hosts would be applicable to other Staphylococcus strains.